2017
DOI: 10.3389/fphar.2017.00614
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Lipegfilgrastim Compared to Pegfilgrastim for the Prophylaxis of Chemotherapy-Induced Neutropenia in Patients with Stage II-IV Breast Cancer

Abstract: Background: Lipegfilgrastim (Lonquex®) has demonstrated to be non-inferior to pegfilgrastim (Neulasta®) in reducing the duration of severe neutropenia (SN) in patients with stage II−IV breast cancer. Compared to pegfilgrastim, lipegfilgrastim also demonstrated statistically significant lower time to ANC recovery in cycles 1–3, lower incidence of SN in cycle 2 and lower depth of absolute neutrophil count (ANC) nadir in cycles 2 and 3. The aim of this study was to quantify the cost utility of lipegfilgrastim com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…Our analysis demonstrated that PEG-rhG-CSF was more costeffective compared to rhG-CSF as primary prophylaxis under the WTP threshold of one-time GDP per capita. The result was similar to Xia et al ( 2020), but different from Akpo et al (2017), Gao and Li (2018), and Li-Tian et al ( 2019), whose results showed that PEG-rhG-CSF strategy was cost-saving than rhG-CSF. Compared to randomized trials, our study showed that the incidence of FN for the short-acting group was higher than these studies, and the cost of the long-acting group was in excess of approximately ¥2,500, but the price gap in Akpo et al (2017) and Gao and Li (2018) was zero.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our analysis demonstrated that PEG-rhG-CSF was more costeffective compared to rhG-CSF as primary prophylaxis under the WTP threshold of one-time GDP per capita. The result was similar to Xia et al ( 2020), but different from Akpo et al (2017), Gao and Li (2018), and Li-Tian et al ( 2019), whose results showed that PEG-rhG-CSF strategy was cost-saving than rhG-CSF. Compared to randomized trials, our study showed that the incidence of FN for the short-acting group was higher than these studies, and the cost of the long-acting group was in excess of approximately ¥2,500, but the price gap in Akpo et al (2017) and Gao and Li (2018) was zero.…”
Section: Discussionsupporting
confidence: 85%
“…The result was similar to Xia et al ( 2020), but different from Akpo et al (2017), Gao and Li (2018), and Li-Tian et al ( 2019), whose results showed that PEG-rhG-CSF strategy was cost-saving than rhG-CSF. Compared to randomized trials, our study showed that the incidence of FN for the short-acting group was higher than these studies, and the cost of the long-acting group was in excess of approximately ¥2,500, but the price gap in Akpo et al (2017) and Gao and Li (2018) was zero. This may be one of the reasons why their results differed from ours.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As a result of its novel pegylation method [ 13 , 14 ], lipegfilgrastim has a different pharmacokinetic and pharmacodynamic profile than pegfilgrastim, specifically higher cumulative exposure and slower clearance, and induces a longer-lasting increase in ANC at equivalent doses [ 15 ]. Analyses utilizing data from patients with breast cancer suggest that lipegfilgrastim is likely to be a cost-effective alternative to pegfilgrastim for primary prohylaxis of complications of chemotherapy-induced neutropenia and associated complications [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%